FTA and PIM research showing the economic benefits of community forest concessions makes the case for continued community stewardship of 400,000 hectares of tropical forests in Guatemala - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
The National Council for Protected Areas issued the revised norms for forest concessions in September 2019 and renewed the first concession contract in December 2019.